2021
DOI: 10.1186/s12934-020-01506-x
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective synthesis of d-amino acids via stereoinversion of corresponding counterpart by an in vivo cascade cell factory

Abstract: Background d-Amino acids are increasingly used as building blocks to produce pharmaceuticals and fine chemicals. However, establishing a universal biocatalyst for the general synthesis of d-amino acids from cheap and readily available precursors with few by-products is challenging. In this study, we developed an efficient in vivo biocatalysis system for the synthesis of d-amino acids from l-amino acids by the co-expression of membrane-associated l-amino acid deaminase obtained from Proteus mira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…A similar study combining PmLAAD whole‐cell with purified StDAPDH H227V and Burkholderia stabilis BsFDH yielded 13.2 g L −1 D‐Phe in 6 h, with 100 % conversion rate and >99 % ee [15] . And more recently, the three enzymes were assembled in one cell and the titer of D‐Phe was improved to 24.7 g L −1 in 24 h by 75 g L −1 whole‐cell catalyst and 15 mM NADP + [23] . A quick cost analysis of our final process from materials and catalyst showed that the cost for D‐Phe production is about $11450 per ton.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A similar study combining PmLAAD whole‐cell with purified StDAPDH H227V and Burkholderia stabilis BsFDH yielded 13.2 g L −1 D‐Phe in 6 h, with 100 % conversion rate and >99 % ee [15] . And more recently, the three enzymes were assembled in one cell and the titer of D‐Phe was improved to 24.7 g L −1 in 24 h by 75 g L −1 whole‐cell catalyst and 15 mM NADP + [23] . A quick cost analysis of our final process from materials and catalyst showed that the cost for D‐Phe production is about $11450 per ton.…”
Section: Discussionmentioning
confidence: 98%
“…[15] And more recently, the three enzymes were assembled in one cell and the titer of D-Phe was improved to 24.7 g L À 1 in 24 h by 75 g L À 1 whole-cell catalyst and 15 mM NADP + . [23] A quick cost analysis of our final process from materials and catalyst showed that the cost for D-Phe production is about $11450 per ton. By contrast, the factory price for D-Phe is as high as $30500 per ton (Table S4).…”
Section: Discussionmentioning
confidence: 99%
“…Additional three enzyme cascades exist geared toward production of non-natural products for the interested reader. [138][139][140][141][142] Notably, Otte et al developed a three enzyme cascade to produce the industrially relevant polymer building block azelaic acid. [142] Additionally, Engelmann et al developed a three enzyme cascade for the production of cinnamyl cinnamate where they demonstrated potential scale-up methods for the production of the highvalue aromatic ester.…”
Section: Other Three-enzyme Cascadesmentioning
confidence: 99%
“…Enantiomers of chiral clinical drugs often exhibit different pharmacological activities or toxicological properties, owing to their different spatial structures [27] . L‐phenylalanine (L‐Phe), an aromatic amino acid, is revealed to be the structural unit of many natural products and drug molecules, [28] and can be used as a drug‐carrier loading drug to directly inject the focal zone and improve drug utilization [29] . Therefore, it is necessary to distinguish the effective enantiomers between different structures of chiral molecules.…”
Section: Introductionmentioning
confidence: 99%